The Importance of Definitions of Data and Observation Frequen-cies for Job and Worker Flows - Norwegian Experiences 1996-1997 - Harald Dale-Olsen; Dag Rønningen (Statistics Norway, Research Department, 2000)
This paper examines the importance of definitions for establishments and for observation frequency for the resulting job and worker flow rates. In particular, this is of importance when comparing results across countries, i.e., in comparative analyses of job and worker flows. Measuring job and worker flow at the firm level, after invoking size limitations or after invoking a correction procedure for taking care of entry and exit due to administrative causes, lowers the job and worker flows compared to job and worker flows measured at establishment level, with no size limitations and no correction procedure. In a comparative analysis of job and worker flows, this shows that job and worker flows in Norway are lower than job and worker flows in many comparable countries.
Keywords: J63; C81; 330